Communication effectiveness in the building maintenance practice of high rise commercial building - Yahya, Mohamad Ridzuan; Abdul Rahim, Asiah; Hj Mohd Ariffin, Noor Aziah; Salleh, Nurul Hamiruddin (2015)
The fundamental problem in building management is to improve an effective communication system among building stakeholders in the operation and maintenance activities. The research objectives are to examine whether proactive communication results in effective communication between maintenance management teams and building occupants and to determine whether reactive communication results in ineffective communication between maintenance management teams and building occupants. This research identified three (3) attributes of the existing condition of communication system in maintenance management specifically safety practice, management quality and professionalism in operation and maintenance management. Twenty (20) high rise commercial buildings in Klang Valley, Malaysia have been randomly selected for the study which involving two (2) groups of respondents. In-house maintenance management personnel (MM) and outsourced teams (OS) are in maintenance management group whereas building owners (BO) and tenants (T) as the building occupant group have been unstructured interviewed based on the value aspects of communication factors. The results had revealed that inaccuracy, untimeliness, misunderstanding, barriers, information gatekeeping, information distortion, information overload and information under load which effected from ineffective communication among participants in the whole level tasks at maintenance stage. In addition, major issues of maintenance management tools: unavailable building policy, poor management of documents, also weak monitoring toward maintenance activities contributed to the insufficient communication system in maintenance management. In conclusion, a systematic and effective communication system among participants does not exist yet at maintenance stage in high rise commercial buildings. Keywords: facilities management, decision support